FRI0515 Neuropilin-1 Contributes to Impaired Angiogenesis in Systemic Sclerosis and Correlates to Clinical Features. (10th June 2014) - Romano, E.; Mazzotta, C.; Manetti, M.; Chora, I.; Bellando-Randone, S.; Bruni, C.; Blagojevic, J.; Ibba-Manneschi, L.; Matucci-Cerinic, M.; Guiducci, S.
Abstract : Background: In systemic sclerosis (SSc) vascular involvement is a primary event characterized by vascular tone dysfunction and increased circulating levels of vascular endothelial growth factor (VEGF). Neuropilin-1 (NRP1) is a receptor for both class-3 semaphorin (sema) family of axon guidance molecules and VEGF. NRP1 is required for optimal VEGF/VEGFR-2 signaling, and NRP1-deficient mice exhibit vascular defects including disorganized blood vessels, lack of normal branching and missing capillary networks. Sema3a controls physiological and pathological angiogenesis. Objectives: In the present study, we investigated the possible involvement of sema3a/NRP1 axis in SSc and its correlation to nailfold videocapillaroscopy (NVC) patterns and digital ulcers. Methods: Soluble NRP1 (sNRP1) and sema3a levels were measured by quantitative colorimetric sandwich ELISA in serum samples from SSc patients (n=49) and age- and sex-matched healthy controls (n=39). Patients were classified according to NVC patterns (early, active and late). NRP1 and sema3a protein expression was evaluated by immunofluorescence and western blot in skin biopsies from SSc patients (n=10) and healthy controls (n=8). NRP1 expression was also evaluated in human dermal microvascular endothelial cells from SSc patients (SSc-MVECs) and healthy controls (H-MVECs) at basal level, and in H-MVECs after stimulation for 24 hours with recombinant human VEGF165 (10 ng/ml), SSc sera (n=3) and healthy sera (n=3). Results: Circulating sNRP1 levels were significantly reduced in SSc patients (median 0.22 ng/ml) compared with healthy controls (median 0.69 ng/ml) (p=0.005). In particular, sNRP1 levels were significantly lower in either SSc patients with active or late NVC patterns than in controls (both p<0.05). Moreover, sNRP1 levels were significantly decreased in SSc patients with digital ulcers compared both with patients without digital ulcers (p=0.009) and controls (p=0.001). No significant differences in sema3a levels were detected between patients and controls. NRP1 expression was decreased in clinically affected skin biopsies from SSc patients compared with healthy skin, especially in dermal endothelial cells and stromal cells. H-MVECs showed higher NRP1 protein expression compared with SSc-MVECs. Stimulation with recombinant VEGF165 strongly upregulated NRP1 expression in H-MVECs. NRP1 expression in H-MVECs increased after treatment with healthy sera compared with basal condition, while it decreased after challenging with SSc sera (both p<0.005 vs basal H-MVECs). Sema3a expression was not different in skin biopsies from SSc patients compared with controls. Conclusions: NRP1 expression is significantly decreased in SSc, and lower sNRP1 levels correlate with the severity of nailfold capillary modifications and presence of digital ulcers. NRP1 might play a role in the vascular damage and in the impairment of the angiogenic process in SSc. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3662